Atypical presentation of thyroid storm: a diagnostic dilemma. Issue 8 (26th August 2019) - Banerjee, Arnab; Bala, Renu; Aggarwal, Richa
Abstract : Thyroid storm (accelerated hyperthyroidism) is an uncommon life-threatening emergency. The diagnosis is difficult and at times delayed owing to atypical presentation. Early diagnosis is the key to its successful management. We came across a patient who had presentations of acute abdomen but later diagnosed in thyroid storm. Multiorgan involvement leads all resuscitative measures futile and prevented us to salvage the patient.